Does the role of family meetings important at the end-of-life? A retrospective national study in Taiwan - Tsung-Hsien Yu; Chung-Jen Wei; Wei-Wen Wu; Frank Leigh Lu (BMC Palliative Care)
Abstract Background Numerous studies have pointed out the benefits of family meetings, but it is unclear who uses family meetings and what the effects are on use of the end-of-life care. Aim The purposes of this study were to explore which characteristics are associated with the use of the family meeting and what effects the family meeting has on end-of-life care. Design A retrospective observational study using 2012–2017 data from Taiwan’s National Health Insurance claims database, cancer registry, and death registry. Setting/participants People who died between 2013 and 2017 in Taiwan as the study population. The deceased people whose information on gender, marital status, or insured classification that was unknown were excluded from this study. Results A total of 792,947 people were included. All demographic characteristics were associated with the use of family meetings, and all demographic characteristics (except for gender and residence area) and hospital characteristics were associated with the initiation time of family meetings. We also found use of family meetings increased the use of hospice care (OR:4.949) and decreased the use of CPR (OR:0.208) at the end of life, initiation time was also associated with the hospice and CPR, but the effects were varied. Conclusion This study demonstrated that family meetings affected the care at end-of-life. Although the utilization of family meeting was increased by year, but also variation still existed among demographic and health characteristics, how to promote it is the next concern in the future.